Kesadaran Hukum Masyarakat terhadap Penerapan Hukum Waris Islam di Desa Pambusuang Kecamatan Balanipa - A Rahim; Auliah Andika Rukman; Resky Amalia Utami (JED (Jurnal Etika Demokrasi), 2019)
The purpose of this research is to find out the level of legal awareness of the Pambusuang Village community towards Islamic inheritance law, and to know the factors that hinder the legal awareness of the community of Pamusuang village towards Islamic inheritance law. The research method used in this study is qualitative field research with an empirical legal approach. In this study using two data sources namely primary data sources and secondary data sources. Methods of data collection in research using observation, interviews and documentation. While the data analysis techniques used are data reduction, data display, and conclusion drawing or verification. The results showed that public legal awareness of the application of Islamic inheritance law in Pambusuang Village, Balanipa Subdistrict tended to impose Islamic inheritance law, although there were still those who joined Islamic inheritance law and customary inheritance law (musyawarah), while the factors that hampered community legal awareness in Pambusuang Village, Balanipa Subdistrict towards the application of Islamic inheritance law namely education factor, its own public awareness factor, the factor of Customary Distribution / Deliberation is considered Fair and the factor is the lack of government role in Pambusuang Village, Balanipa District.Keywords : Community Law Awareness, Islamic inheritance law.